Between pragmatism and the defence of a “Sister State” : the national association for the advancement of colored people and the U.S. occupation of Haiti, 1915-1922 - Belony, Lyns-Virginie (Université de Montréal, 2016)
Initially, the news of the U.S. occupation of Haiti in 1915 generated little concern in the United States. Indeed, Haiti’s political instability made it such that a U.S. intervention seemed unavoidable. As of 1915 and especially 1920, the National Association for the Advancement of Colored People (NAACP), founded in 1909, denounced the U.S. interference in the Caribbean island. W.E.B. Du Bois and James Weldon Johnson, two of the association’s most influential black members, were deeply invested in condemning the U.S. occupation of Haiti. Historiographical tendencies have long located the NAACP’s engagement with Haiti in a conversation about black solidarity, but have failed to adequately consider the local politics that may have inspired the NAACP’s work. While this thesis does not refute the importance of black solidarity, it does recognise the limits of this conceptual approach in trying to explain the complexity of the NAACP’s work on the behalf of Haiti’s sovereignty. Placing more attention on the social and political context in the United States between 1915 and 1922 reveals that the NAACP utilised the occupation of Haiti as a means of attracting broader attention to domestic issues affecting black Americans, but also as a means of reinforcing the organisation’s own profile in the United States.
Keywords: 1915; =CL; Black internationalism; Black solidarity; Haïti; History - Black / Histoire des Noirs (UMI : 0328); Internationalisme noire; NAACP; Occupation Américaine d'Haïti; Solidarité noire; US Occupation of Haiti